ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA PRODUK DI PASAR UNTUK MENCAPAI KEUNGGULAN BERSAING BERKELANJUTAN - Totok Wibisono (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This research analyzes the effect of innovation orientation, promotion support and sales person support to product performance at market in order to enhance sustainable competitive advantage. The formulation problems in this research are to show the effect of innovation orientation to product performance on market, sales person support to product performance on market, promotion support to product performance on market, each construct with sustainable competitive advantage through product performance at market. The variables and indicators of research based on the previous research. There is a model that have been developed and four hypotheses to answer these research problems.            Population of this research is Dealers managers of Toyota Avanza in Central Java amount 130 persons. This research using census method. Data analyze tools which used in this research is Structural Equation Modeling (SEM) under AMOS 4.01 program.            Result from data analyzes shows that the model and the result from research can be accepted. And that this result proves that innovation orientation have an positive and significant effect to product performance on market, and next make an abbreviate in the support from sales person with product performance on market are influence by product performance on market, thus can make an conclusion that each constructs have an empiric evidence and the justification with sustainable competitive advantage through performance of product on market in a positive and significant influence